ENGINEERING DEVELOPMENT OF TELESCOPE CONTROL SYSTEMS - Ivanov, V. N.; Ryabov, A. V.; Pereversentsev, A. F. (Одеські астрономічні публікації, 2017)
Advantages are presented in the use of stepping motors with electron drives, developments and investigations of them at the Observatory throughout recent years.